WASTE MANAGEMENT IN SUPPORTING SUSTAINABLE TOURISM CASE STUDY OF TOURIS DESTINATION MALIOBORO YOGYAKARTA - Ripno Ripno; Theodosia C. Nathalia; Rudy Pramomo (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
In general, waste is defined as the result of human activities and natural processes in solid or liquid form. Waste that is not managed properly can cause various problems in various sectors, one of which is the tourism sector. The purpose of this study is to determine the perceptions of tourism stakeholders and waste management management in the tourist area of Malioboro. This study used a descriptive qualitative method with FGD, observation and unstructured interviews as techniques in data collection. The researcher uses George R. Terry's theory where management consists of 4 (four) factors, namely Planning, Organizing, Actuating, and Controlling. The results of this study state that waste management in Malioboro tourist destinations is carried out well, this is evidenced by the implementation or fulfillment of these 4 (four) factors. Suggestions from this research, it is hoped that related agencies dealing with solid waste can improve the current deficiencies, both in terms of human resources, completeness of existing facilities and infrastructure